2014
DOI: 10.1002/pola.27195
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of perfluoro-1,3-propanedisulfonic acid/Nafion/silica hybrid nanoparticles-thermally stable Nafion in these silica hybrid nanoparticles even after calcination at 800 °C

Abstract: Perfluoro‐1,3‐propanedisulfonic acid (PFPS)/Nafion/silica hybrid particles were prepared by the sol–gel reactions of PFPS with tetraethoxysilane and silica nanoparticles in the presence of Nafion under alkaline conditions. These obtained composites exhibited a good dispersibility and stability in not only water but also traditional organic media such as methanol, ethanol, 1,2‐dichloroethane, tetrahydrofuran, and dimethyl sulfoxide. Dynamic light scattering measurements and field‐emission scanning electron micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…In fact, we have already succeeded in preparing new fluoroalkyl end-capped oligomer/silica nanocomposites through the encapsulation of silica nanoparticles as guest molecules into fluoroalkyl end-capped oligomeric nanoparticle cores, and fluoroalkyl end-capped oligomers containing higher acidic protons such as sulfo groups formed by the nanocomposite reactions in the presence of tetraethoxysilane (TEOS) and silica nanoparticles under alkaline conditions afforded no weight loss behavior at 800°C; although the corresponding oligomer containing carboxyl groups can exhibit a usual weight loss after calcination corresponding to the content of the oligomer in the composite matrices [28]. Low molecular weight fluorinated surfactants such as perfluoro-1,3-propanedisulfonic acid (PFPS) were also applied to the nanocomposite reactions with TEOS in the presence of silica nanoparticles under alkaline conditions to give no weight loss corresponding to the content of PFPS in the silica nanocomposite cores even after calcination at 800°C [29,30]. It was suggested that the smooth dehydrofluorination between the sulfonic acid protons (higher acidic protons) and fluorines in fluorinated oligomers catalyzed by both ammonia and silica nanoparticles should proceed to give hydrogen fluoride, and this hydrogen fluoride can react with silica nanoparticles to afford ammonium hexafluorosilicate [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, we have already succeeded in preparing new fluoroalkyl end-capped oligomer/silica nanocomposites through the encapsulation of silica nanoparticles as guest molecules into fluoroalkyl end-capped oligomeric nanoparticle cores, and fluoroalkyl end-capped oligomers containing higher acidic protons such as sulfo groups formed by the nanocomposite reactions in the presence of tetraethoxysilane (TEOS) and silica nanoparticles under alkaline conditions afforded no weight loss behavior at 800°C; although the corresponding oligomer containing carboxyl groups can exhibit a usual weight loss after calcination corresponding to the content of the oligomer in the composite matrices [28]. Low molecular weight fluorinated surfactants such as perfluoro-1,3-propanedisulfonic acid (PFPS) were also applied to the nanocomposite reactions with TEOS in the presence of silica nanoparticles under alkaline conditions to give no weight loss corresponding to the content of PFPS in the silica nanocomposite cores even after calcination at 800°C [29,30]. It was suggested that the smooth dehydrofluorination between the sulfonic acid protons (higher acidic protons) and fluorines in fluorinated oligomers catalyzed by both ammonia and silica nanoparticles should proceed to give hydrogen fluoride, and this hydrogen fluoride can react with silica nanoparticles to afford ammonium hexafluorosilicate [31][32][33].…”
Section: Introductionmentioning
confidence: 99%